MANAJEMEN SUMBER DAYA MANUSIA DI KANTOR KECAMATAN KANGAYAN - Hamka; Satunggale Kurniawan; Rahman, Muhammad Afifi (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
HR (Human Resources) development in sub-district offices refers to efforts to improve the quality, capacity and performance of employees working at the sub-district level. HR development is a strategic process that involves various activities and programs to strengthen the capabilities of individuals, teams and the organization as a whole. The aim is to improve efficiency, effectiveness and services provided to the community. Human resources are one of the most important assets for an organization/company. The role of human resources for organizations/companies is not only seen from the results of work productivity but also seen from the quality of work produced, even further, the superiority of an organization/company is also determined by the superiority of its human competitiveness, not determined by its natural resources. The stronger the knowledge of human resources, the stronger the company's competitiveness. Improving the quality of human resources, and therefore, this paper draws a conclusion, namely "Human Resource Management in the Kangayan District Office". Based on the introduction outlined above, the problem formulation that can be taken is how to manage and empower existing human resources in the Kangayan sub-district office so that it has benefits and functions even though the existing human resources are very limited, it can be achieved through the human resource development process, Human Resource Management (HRDM) is very closely related to HR in an organization or company. HRM itself has many benefits and functions and is useful in managing and empowering existing human resources who are planning to join an organization or company.